Solitary rectal ulcer syndrome in children - Kırıştıoğlu, İrfan and Balkan, Emin and Kılıç, Nizamettin and Doğruyol, Hasan (The Turkish Journal of Pediatrics, 2000)
The solitary rectal ulcer syndrome (SRUS) is an unusual disorder in childhood. Although well recognized in adult literature, the pediatric experience with this condition is limited, so SRUS often goes unrecognized or misdiagnosed. There are very few pediatric case reports in the English literature. This report describes four patients who presented with rectal bleeding, constipation, mucous discharge, and lower abdominal pain, with a diagnosis of SRUS. The diagnosis was made by rectoscopy, defecogram, anorectal manometry and histopathological evaluation. In two patients, defecogram showed a rectocele with both, the sphincter failed to relax to voluntary squeeze pressure on anorectal manometric examination. the histopathological finding in all patients was fibrous obliteration of the lamina propria with disorientation of muscle fibers. all of the patients responded well to conservative therapy, which included defecation training, laxatives, sulfasalazine, and application of rectal sucralfate enema, and remained asymptomatic on the follow-up. Although rare in the pediatric population, SRUS should be relatively easy to recognize in the child with rectal bleeding, after elimination of other causes. If suspected, the diagnosis of SRUS may be made at endoscopy and confirmed by rectal biopsy.